2018
DOI: 10.31449/inf.v42i4.1132
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Estimation of News Values Reflecting Importance and Closeness of News Events

Abstract: This paper addresses a problem of automatic estimation of three journalistic news values, more specifically frequency, threshold and proximity, by applying various text mining methods. Although theoretical frameworks already exist in social sciences that identify if an event is newsworthy, these manual techniques require enormous amount of time and domain knowledge. Thus, we illustrate how text mining can assist journalistic work by finding news values of different international publishers across the world. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…One of the key contributions of this article is a module for finding trigger words in news. Belyaeva et al [7] suggested that the number of publishers can be used as an indicator when evaluating the importance of news. Therefore, this study adopts three methods to extract trigger words and proposes a method named the 'pyramid relation algorithm' to obtain event relation words.…”
Section: Trigger Words Modulementioning
confidence: 99%
See 2 more Smart Citations
“…One of the key contributions of this article is a module for finding trigger words in news. Belyaeva et al [7] suggested that the number of publishers can be used as an indicator when evaluating the importance of news. Therefore, this study adopts three methods to extract trigger words and proposes a method named the 'pyramid relation algorithm' to obtain event relation words.…”
Section: Trigger Words Modulementioning
confidence: 99%
“…Accordingly, this study aims to extract the features and words from news datasets that are considered valuable by the news media. However, there is much related research that uses text analysis techniques to deal with the vast amounts of news for topic classification or clustering [1,4,[7][8][9][10][11]. Classification is the process of categorising data with the help of class labels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, news angles have not yet been investigated in the research literature from a computational perspective, with the notable exception of the aforementioned work on automatic news classification with respect to news values [5], [6]. In the media industry, the IPTC's NewsML G2, EventsML G2, and rNews formats [21] and the BBC ontologies (https://www.bbc.co.uk/ontologies) offer standards for representing and exchanging news-related information; however, none of them considers news angles.…”
Section: Computational Analyses Of News Anglesmentioning
confidence: 99%
“…Finding good angles on potentially newsworthy events and situations is therefore an important journalistic task, which needs to be better supported by journalistic software tools and platforms. However, although news angles and related concepts are well covered in the journalism literature on a general level, there has been so far only limited computational treatment of these notions, which has primarily focused on the automatic identification of the related notion of news values 1 in journalistic content [5], [6]. In particular, a comprehensive framework for representing and reasoning with news angles is still missing.…”
Section: Introductionmentioning
confidence: 99%